FRIENDSHIP STORIES, CONFLICTS, AND SOLUTIONS (Ustozlar uchun, 2025)
This article explores the psychological foundations of friendship, focusing on how friendships form, why conflicts arise, and how they can be effectively resolved. Drawing from research in social psychology, neuroscience, and conflict studies, it explains that deep friendships develop through shared vulnerability, oxytocin-based bonding, neural synchrony, and repeated low-pressure interactions. The article highlights that most friendship conflicts stem from expectation gaps and cognitive biases rather than intentional harm. It examines how the brain processes social pain similarly to physical pain, which intensifies emotional reactions during friendship tensions.